A gravity approach of agricultural trade:the nexus of the EU and African, Caribbean and Pacific countries - Balogh, Jeremiás Maté (2020)
The European Union (EU) is one of the biggest traders of agricultural products. In 2017, extra-EU agricultural trade accounted for 7.4% of the total EU international trade. Furthermore, Europe is the main destination for agricultural goods arriving from African, Caribbean and Pacific (ACP) trading partners. The paper analyses the effect of geographical proximity, cultural similarity, free trade agreements on bilateral agricultural trade as well as intra-industry trade between EU member states and its trading partners (intra and extra EU trade), employing gravity model for a period of 1996–2017. Regression results suggest that EU countries export more agricultural products to their common markets. In addition, the export costs of agricultural products are lower if the EU and its external trading partners are culturally similar; have the same religion or both have regional trade agreements. We found a moderate intra-industry trade between the EU and ACP countries at 18%. The results indicate rather inter-industry trade between EU and non-EU members, with a lower index level for ACP countries. A higher positive impact is revealed on the agricultural import between ACP-EU countries than export.